FUNCTIONAL CATEGORIES OF CODE SWITCHING BY BAJO STUDENTS IN ENGLISH FOREIGN LANGUAGE CLASSROOM - Lalu Erwan Husnan (Aksara, 2016)
AbstractThis research discusses functional categories of codeswitching in English Foreign Language (EFL) classroom by Bajo students at MTs NW Nurul Ihsan Tanjung Luar village. Bajo students use Bajo, Sasak, and Indonesian (multilingual) in their daily communication. They bring their languages into their English classroom when they meet other students who come from other ethnic backgrounds and are only able to speak Sasak and Indonesian. This study is aimed at finding out the functional categories of codeswitching in Bajo’s EFL classroom. Data are collected using observation, interview, and recording method. Method used to analyze the data is descriptive-qualitative by labeling, transcription, classification, and simple descriptive statistic. Result of this research shows that the highest functional categories of codeswitching in the form of pupils’ comment as much as 44% with 129 instances, categorized into less dominant. Grammar explanation is 20% with 58 instances, categorized into not dominant. The other categories are categorized into not dominant. Most of the functional categories of codeswitching use Indonesian as much as 50,68% with 148 instances, categorized into dominant, while English is about 34,59% with 101 instances, categorized into less dominant. The other two languages, Bajo is about 8,22% and Sasak is about 6,51%, are not dominant.